1983
DOI: 10.1139/b83-235
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic differences in the seasonal pattern of net photosynthesis in Cladonia stellaris

Abstract: Despite the contrasting thermal and light environment of sun and shade ecotypes of Cladonia stellaris, analysis of the pattern of net photosynthesis throughout the year as well as enzyme polymorphism in each morphotype has found little genotypic difference. The large disparity between photosynthetic capacity in the sun and shade replicates is shown to be due to a difference in chlorophyll content. There is a significant decline in photosynthetic capacity in November and this is shown to be reversible uncouplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Studies correlating enzymatic variation with population or morphotype variability have also met with limited success. Kershaw et al (1983) and MacFarlane et al (1983) found minimal differences in acid phosphatase, PGI, MDII and leucine amino pepsidase stains in distinct sun and shade populations ot Cfadoitta rangtferiita and C. stellaris. I'ahselt & Hageman (1983) found little difference between isolated stands of (\^traria arenaria, while the highly \ariable morphology of Cladonia cristatella appears to be unrelated to electrophoretic differences (Fahselt, 1986).…”
Section: T S C Ir S S I O Nmentioning
confidence: 95%
See 3 more Smart Citations
“…Studies correlating enzymatic variation with population or morphotype variability have also met with limited success. Kershaw et al (1983) and MacFarlane et al (1983) found minimal differences in acid phosphatase, PGI, MDII and leucine amino pepsidase stains in distinct sun and shade populations ot Cfadoitta rangtferiita and C. stellaris. I'ahselt & Hageman (1983) found little difference between isolated stands of (\^traria arenaria, while the highly \ariable morphology of Cladonia cristatella appears to be unrelated to electrophoretic differences (Fahselt, 1986).…”
Section: T S C Ir S S I O Nmentioning
confidence: 95%
“…Thus studies must rely on field obseryations and shortterm manipulations of thalli collected from the field. Often, the experiments are designed such that comparisons are made between diflerent populations of the lichen species (Kershaw et al, 1983 ;MacFarlane, Kershaw & Webber, 1983;Brown & Kershaw, 1984), These populations are defined on an ecological basis, usitig characteristics such as geographic location, morphology and microsite yariation. Sexual recombination in lichens is thought to be infrequent, the main reproductive outlet being yegetative propagation via fragmentation, isidia or soredia.…”
Section: N T R O D L! C T 1 O Nmentioning
confidence: 99%
See 2 more Smart Citations
“…There are two distinct ecotypes, one characteristic of full solar radiation conditions and the other characteristic of dense shade under virtually closed canopy conditions. The parallel study which is reported elsewhere (Kershaw, MacFarlane and Webber, 1983) contrasts two equivalent ecotypes of C. stellaris from under closed spruce canopy and completely open lichen woodland in northern Ontario. In both situations, sun and shade ecotypes have been examined in terms of their seasonal patterns of gas exchange in parallel with an examination of the potential polymorphism of a number of selected enzymes.…”
Section: Introductionmentioning
confidence: 92%